1976
DOI: 10.1139/f76-008
|View full text |Cite
|
Sign up to set email alerts
|

Ration, Growth, and Measures of Somatic and Organ Condition in Relation to Meal Frequency in Winter Flounder, Pseudopleuronectes americanus, with Hypotheses Regarding Population Homeostasis

Abstract: Six ration levels were established among 120 large, adult winter flounder (Pseudopleuronectes americanus) by setting different feeding frequencies, but with unlimited feeding at each meal. All fish were maintained at 7 C. With decrease in feeding frequency, fish ate less food per month but more food per meal — i.e. ration compensation was attempted. At the lowest frequency, two meals per month, fish did not compensate. At any one feeding frequency, fish ate progressively more per meal from the first to the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
1
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 18 publications
13
108
1
8
Order By: Relevance
“…As shown on Table 2, the spawning period in Çaygören Dam Lake is similar to the previous investigations [30,[41][42][43], except for those in Keddara Dam Lake [23] and Keith and Allardi [44]. The hepatosomatic index is an indicator of feeding activity of fish [45]. It shows an allocation of energy to the liver during every period except reproduction, when part of the energy is used for gonad maturation [46].…”
Section: Discussionsupporting
confidence: 81%
“…As shown on Table 2, the spawning period in Çaygören Dam Lake is similar to the previous investigations [30,[41][42][43], except for those in Keddara Dam Lake [23] and Keith and Allardi [44]. The hepatosomatic index is an indicator of feeding activity of fish [45]. It shows an allocation of energy to the liver during every period except reproduction, when part of the energy is used for gonad maturation [46].…”
Section: Discussionsupporting
confidence: 81%
“…According to Tyler and Dunn (1976) Adams et al, 1992). Rypel and Bayne (2010) evaluated growth rates of six fish species correlated with PCB concentrations in a moderatelyto-heavily polluted freshwater ecosystem, and concluded that at the range of concentrations investigated, these PCBs do not exert negative impacts on growth.…”
Section: Discussionmentioning
confidence: 99%
“…Simple regression analyses on growth showed significant coefficient of determination (R 2 ) in the three feeding rates, in relation to final weight (R 2 = 0.84), final length (R 2 = 0.82), ADGR (R 2 = 0.80) and SGR (R 2 = 0.84), indicating that growth can still be improved with increasing amount of food. Tyler and Dunn (1976) Seenappa and Devaraj (1991) also observed increases in the growth of Chanos chanos and Cirrhinus mrigala with increased feeding rates. Nour, et al, (1993) also found similar trend in Mugil cephalus fingerlings.…”
Section: Discussionmentioning
confidence: 93%